Democracy, Law, and Comparative Politics - Guillermo O’Donnell (My University, 2016)
This article offers a revision of democratic theory in light of the experience of recently democratized countries, located outside of the northwestern quadrant of the world. First, various definitions of democracy that claim to follow Schumpeter and are usually considered to be “minimalist” or “processualist” are critically examined. Building upon but clarifying these conceptual efforts, a realistic and restricted, but not minimalist, definition of a democratic regime is proposed. Thereafter, this article argues that democracy should be analyzed not only at the level of the political regime but also in relation to the state—especially the state qua legal system—and to certain aspects of the overall social context. The main underlying theme that runs through this article is the concept of agency, especially as it is expressed in the legal system of existing democracies.